Analysis of Romania's and Transylvania's Tourist Supply Development and Performance - Monica Maria Coroș; Adina Letitia Negrușa (Amfiteatru Economic Journal, 2014)
The paper's premise is that a strong link exists between Romania's poor tourism performance and the quality of its hospitality supply. In this respect, a comparative analysis of Romania's and Transylvania's tourist offering is carried out aiming at identifying the particularities of their development and the causes of their poor performance. The motivation for having chosen Transylvania resides in this region's attractiveness among foreign tourists; it is a destination with a high potential favoring the development of some tourist products competitive on the international market. Thus, based on a comprehensive secondary data analysis regarding the public lodging facilities, the paper presents their geographic dispersion, the development of the accommodation capacity by levels of classification, the number of available beds, the types of units, the structures' international affiliation, the main Romanian owners, etc. The dispersion by levels of classification, together with the net usage indexes of the accommodation capacity, characterize the performance of this industry. The research study emphasizes the fact that despite a high tourist potential, the present-day hospitality supply cannot support a healthy development of the tourist activity, and presents some possible causes.
Keywords: C46; L83; 330; tourism supply; hospitality; development; performance; hotel owners and